The PENGARUH KONVERSI BANK KONVENSIONAL MENJADI SYARIAH TERHADAP MINAT PNS UNTUK BERTRANSAKSI SOSIAL EKONOMI PADA BANK NTB SYARIAH (STUDI KASUS PNS DI KECAMATAN LANGGUDU) - Bustamil, Bustamil; Nurwahidin, Nurwahidin (Program Studi Ekonomi Syariah IAI Muhammadiyah Bima, 2023)
This study aims to determine whether the conversion of conventional banks to Islamic banks has a significant effect on the interest of civil servants in the Langgudu sub-district to carry out socio-economic transactions at Bank NTB Syariah. The total population in this study was 174 civil servants in Langgudu District, while the number of samples in this study were 100 people who were taken using the Slovin formula. The calculation process uses STATA version 17. The results of the study show that cultural variables partially have no effect on the interest of civil servants to transact at Bank NTB Syariah because they have a significance value of 0.584. However, if testing is carried out simultaneously the Cultural Variables, Religiosity, and Knowledge affect the interest of Civil Servants to carry out socio-economic transactions at Bank NTB Syariah with an r Square value of 0.23. This means that 23% of the interest of Civil Servants to transact at Bank NTB Syariah is influenced by Culture, Religiosity and Knowledge and the remaining 76.1% is influenced by other factors not mentioned in this study.